A Conceptual and Applied Study of Trividha Karma in Shalya tantra - Gupta, Anshuma; Singh, Sudha (International Research Journal of Ayurveda & Yoga, 2022)
All types of Ayurvedic treatments are described under Ashtang Ayurveda which means eight branches of Ayurveda. Shalya tantra is one of them and Sushruta Samhita is the oldest text available on Shalya Tantra (surgery). The Sushruta Samhita acts as a training manual and educative text for surgery, and enabled a move away from the more primitive forms of surgery practiced beforehand. Many procedures and methods of surgery were described and in some way acts as a basic manual from which surgery in the modern day has grown from.Sutra Sthana of Sushruta Samhita deals with basic concepts of surgery, surgical instruments and appliances, practical training, duties of the surgeon, Sandhan Karma, causes and classification of diseases etc.Being a surgeon Acharya Sushruta was well aware about the complications of surgery so before talking anything about the surgery first he told about the concept of Trividh Karma i.e. poorva karma means accessories to be obtained before the commencement of main surgical procedure, pradhan karma means main surgical procedure, paschat karma means measures that should be taken to cure the patient after main surgical procedure until the patient is discharged.